Effects of team competition-based training on petanque pointing accuracy among university athletes - Muhammad Faisal Ansari Nasution; Junaidi; Heni Widyaningsih (Journal of Coaching and Sports Science, 2026)
Background: Pointing accuracy is a central performance skill in petanque because successful pointing determines boule proximity to the jack and shapes scoring opportunities during match play. However, conventional university practice often emphasises isolated technical repetition, whereas competition requires accuracy under time, peer, and outcome pressure. Purpose: This study compared Team Competition-Based Training (TCBT) with Standard Training (ST) for improving petanque pointing accuracy among university athletes. Methods: A course-based quasi-experimental pretest-posttest control-group design was implemented with 50 students. Participants were allocated to TCBT (n = 25) or ST (n = 25). Both groups completed 16 structured sessions over eight weeks. The technical content, duration, equipment, and training frequency were matched; only the organisational format differed. Pointing accuracy was measured at 6 m using a 0-15 scoring protocol. Results: Both groups improved significantly from pre-test to post-test. The TCBT group improved from 2.32 +/- 1.35 to 7.40 +/- 1.47, whereas the ST group improved from 2.24 +/- 1.30 to 6.20 +/- 1.38. The post-test between-group difference favoured TCBT, t(48) = 2.969, p = .005, mean difference = 1.20 points, 95% CI [0.39, 2.01], Cohen's d = 0.84. Conclusion: Within the limits of a single-university sample and an immediate post-test design, TCBT produced greater short-term improvement in pointing accuracy than ST. The findings support the cautious integration of competition-like team formats into university petanque training.